The Influence of Job Satisfaction, Work Supervision and Work Discipline on the Performance of PT Employees Indah Pontjan District Serdang Bedagai (Case study of Penunasan employees) - Hermina Capah; Yohny Anwar (Yayasan Multidimensi Kreatif, 2024)
This research was conducted at PT. Indah Potjan with the aim of finding out the effect of job satisfaction, work supervision and work discipline on employee performance. The population is 110 employees who work in the company in the Penunasan section by random sampling using the Slovin formula to obtain a research sample of 52 people. The types of data used are primary and secondary data, data collection techniques using questionnaires, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption testing and hypothesis testing. The results of the research show that: 1) job satisfaction has a partial positive but not significant effect on employee performance, 2) work supervision has a partial positive and significant effect on employee performance, 3) work discipline has no positive and insignificant effect on employee performance. Simultaneously, job satisfaction, work supervision and work discipline have a significant effect on employee performance. There is a strong correlation between job satisfaction, work supervision and work discipline and performance and the percentage of 50.9% of employee performance can be explained by job satisfaction, work supervision and work discipline and the remaining 49.1% can be explained by other variables not studied.